The entrepreneur's guide to risk and decisions : building successful early-stage ventures - Pittz, Thomas G.; Liguori, Eric W. (Emerald Publishing Limited, 2020)
Becoming a successful entrepreneur is impossible without accepting risk - the question is which risk to take and at what time. Expert authors Thomas G. Pittz and Eric W. Liguori draw on years of working with and in early-stage ventures to provide guidance for managing the risk associated with these decisions. Throughout this book, they offer practical, no-nonsense advice for marketing and financing your business, bringing on partners and employees, networking with key connectors, and launching your business as inexpensively and aggressively as possible. Following lean startup logic, The Entrepreneur's Guide to Risk and Decisions: Building Successful Early-Stage Ventures cuts through to the strategically important - and emotionally charged - decisions that separate the successful entrepreneurs from the unsuccessful. It is designed to help entrepreneurs move quickly, rapidly iterate their business models based on customer feedback, and provide guideposts for managing the risks inherent in all startup ventures.- Resumé vydavatel
Includes index.
Keywords: rozhodování; rizikový management; podnikání; malé a střední podniky; decision making; risk management; business; small and medium-sized enterprises; elektronické knihy; monografie; electronic books; monographs